Compresive Strengths And Modulus Of Elasticity Of Steel Fiber Reinforced Concrete Under Different Temperature Conditions - Masoud, Mohamed Alfitouri; , Dr. M. Solikin, M.T; , Yenny Nurchasanah, S.T., M.T (2015)
The aim of this study is to investigate the strength and modulus of elasticity progress of steel fiber reinforced concrete under different temperature condition on difference fibers volume fractions: 1) to analyze the compressive strength and modulus of elasticity of steel fiber reinforced concrete on volume fractions of 1% fiber at three temperature levels of 200oC, 400oCand 600oC; 2) to analyze the compressive strength and modulus of elasticity of steel fiber reinforced concrete on volume fractions of 1.5% fiber at three temperature levels of 200oC, 400oC and 600oC; and 3) to analyze the comparison of the compressive strength and modulus of elasticity at concrete without fibre on the same temperature. This study will compare the compressive strength and modulus elasticity between plain concrete and SFRC containing various volume fraction of steel fiber as reinforcement on elevated temperature heating up to 600°C is subjected to some concrete and SFRC specimen. Material test aims to find out the quality of the material before making the concrete specimen. In this study conduct kinds of test, i.e. 1) Basic Material Test; 2) Compressive Strength; and 3) Modulus of Elasticity. The data analysis was conducted after testing of a specimen by comparing and analyzing the data obtained. The tests was performed compressive test and modulus of elasticity. From the research findings can be concluded that 1) The addition of 1% and 1.5% steel fiber in concrete mix is advantageous for concrete; 2) Overall the compressive strength of concrete was increased as the percentage of steel fiber in concrete increases. Up to 1.5% , Steel fiber reinforced concrete showed a better overall residual strength and better crack resistance than non-fiber concrete; 3) The carbonation process for concrete with steel fiber is a little influenced by temperature compare to concrete without steel fiber; and 4) The concrete with 1.5 % steel fiber demonstrated the highest compressive and modulus of elasticity value, 23.5 and 17172 MPa at 6000C respectively. It is expected that in future concrete having steel fiber will act as a fire protective considerably